2005
DOI: 10.1105/tpc.104.026435
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Arabidopsis WRKY DNA Binding Domain

Abstract: The WRKY proteins comprise a major family of transcription factors that are essential in pathogen and salicylic acid responses of higher plants as well as a variety of plant-specific reactions. They share a DNA binding domain, designated as the WRKY domain, which contains an invariant WRKYGQK sequence and a CX 4-5 CX 22-23 HXH zinc binding motif. Herein, we report the NMR solution structure of the C-terminal WRKY domain of the Arabidopsis thaliana WRKY4 protein. The structure consists of a four-stranded b-shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 49 publications
8
171
1
1
Order By: Relevance
“…The structure of the C-terminal WRKY domain of the Arabidopsis thaliana WRKY4 protein consists of a central four-stranded β-sheet, with a zinc binding pocket formed by conserved Cys/His residues located at one end of the β-sheet. Further biochemical results suggest that this zinc finger should be responsible for WRKY DNA binding, through which the zinc finger and the conserved WRKYGQK motif enters the DNA groove and forms contacts with the DNA bases (Yamasaki et al, 2005). The result of Secondary Structure Matching (Krissinel and Henrick, 2004) indicates that the central four strands of the SNAC1 NAC domain shares a high structural similarity with the four-stranded β-sheet of WRKY domain.…”
Section: Dimeric Assembly Of Snac1 Nac Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the C-terminal WRKY domain of the Arabidopsis thaliana WRKY4 protein consists of a central four-stranded β-sheet, with a zinc binding pocket formed by conserved Cys/His residues located at one end of the β-sheet. Further biochemical results suggest that this zinc finger should be responsible for WRKY DNA binding, through which the zinc finger and the conserved WRKYGQK motif enters the DNA groove and forms contacts with the DNA bases (Yamasaki et al, 2005). The result of Secondary Structure Matching (Krissinel and Henrick, 2004) indicates that the central four strands of the SNAC1 NAC domain shares a high structural similarity with the four-stranded β-sheet of WRKY domain.…”
Section: Dimeric Assembly Of Snac1 Nac Domainmentioning
confidence: 99%
“…NAC transcription factors belong to the second largest family of the plant-specific transcription factors together with NAM, ATAF1,2, and CUC2 (cup-shaped cotyledon), sharing a conserved DNA binding domain of~150 amino acids in length named as the NAC domain (Hu et al, 2006). WRKY proteins comprise another transcription factor family, which are essential in pathogen and salicylic acid responses of higher plants (Yamasaki et al, 2005). WRKY proteins share a highly conserved DNA binding domain known as the WRKY domain, which consists of a CX 4-5 CX 22-23 HXH zinc binding motif and a conserved WRKYGQK sequence (Yamasaki et al, 2005).…”
Section: Dimeric Assembly Of Snac1 Nac Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…In the solution structure description by Yamasaki et al (2005) it became clear that the wRKY domain constitutes a four-stranded β-sheet, with a zinc-binding pocket formed by the conserved Cys/His residues. The wRKY signature sequence enters the major groove of DNA and binds to its cognate DNA-binding site (TTGACC/T) known as the w box (Yamasaki et al 2005). A few years later, a crystal structure description of the AtwRKY1 C terminal wRKY domain showed a similar structure (Duan et al 2007).…”
Section: Wrky Transcription Factors-domain Structure and Bindingmentioning
confidence: 99%
“…WRKY family members are divided into three groups based on the number of WRKY domains and certain features of the zinc finger-like motifs (Eulgem et al, 2000). The NMR solution structure revealed that the C-terminal WRKY domain of Arabidopsis WRKY4 consists of a four-stranded b-sheet, with a zinc-binding pocket formed by the conserved Cys/His residues located at one end of the b-sheet, and the WRKYGQK residues, corresponding to the most N-terminal b-strand (strand b-1), kinked in the middle of the sequence by the Gly residue (Yamasaki et al, 2005). The concave curvature of strand b-1 induced by this kink is predicted to enable this strand to deeply enter the DNA groove and make contact with bases of the W box element.…”
Section: The Wrky Factorsmentioning
confidence: 99%